2008
DOI: 10.1017/s0033291708004716
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous movement disorders in antipsychotic-naive patients with first-episode psychoses: a systematic review

Abstract: These findings support the notion that spontaneous abnormal movements are part of a neurodysfunction intrinsic to the pathogenesis of schizophrenia. Future studies should further investigate the role of basal ganglia and extrapyramidal pathways in the pathophysiology of psychosis, with particular attention to treatment implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
174
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(191 citation statements)
references
References 80 publications
13
174
0
4
Order By: Relevance
“…Abnormal, involuntary movements in schizophrenia have been extensively reviewed [10,11,13,54]. Spontaneous and tardive dyskinesias (TD) comprise abnormal, involuntary, repetitive movements of the orofacial, limb, trunk, and respiratory musculature [54].…”
Section: Clinical Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Abnormal, involuntary movements in schizophrenia have been extensively reviewed [10,11,13,54]. Spontaneous and tardive dyskinesias (TD) comprise abnormal, involuntary, repetitive movements of the orofacial, limb, trunk, and respiratory musculature [54].…”
Section: Clinical Perspectivesmentioning
confidence: 99%
“…Recent reviews have addressed the nosological problems concerning catatonia [6,7,8], the meaning of abnormal involuntary movements and neurological soft signs (NSS) in schizophrenia [9,10,11], psychomotor slowing [12], and motor deficits or neurological abnormalities in antipsychotic naïve schizophrenia patients [10,13,14]. Since these reviews focused on specific aspects of motor deficits or on special populations, a comprehensive view of motor phenomena is difficult to develop, since the descriptions, definitions, and interpretations vary largely with the conceptual frameworks [15].…”
Section: Introductionmentioning
confidence: 99%
“…We found similar results in our model, and a possible explanation for this might be the presence in our sample of some first-episode patients (14.72%), who can be more susceptible to the effect of antipsychotics. 14 Pappa & Dazzan, 15 in a systematic review, alternatively suggested that, although dyskinesia and Parkinsonism can be induced by antipsychotics, in drug-naïve individuals they could also be the result of neurologic dysfunction related to the pathogenesis underlying the illness. Either way, first-episode patients could be more vulnerable to motor symptoms, which may have biased previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…6,16 Diskinetik hareketler, özellikle orofasiyal olanlar yaşlı bireylerin %5 ila 15'inde, antipsikotik naif şizofreni hastalarının yaklaşık %7'sinde izlenebilir. 17 İnsidansı antipsikotik tedavi süresi uzadıkça, her yıl için yaklaşık %3-5 oranında birikerek artar; yaklaşık %20-25 gibi bir değere ulaşır. 6,16 Antipsikotik ilaçların kesilmesi, değiştirilmesi ya da dozlarının azaltılmasından sonra iki hafta içinde gelişen veya önceden var olan hareket bozukluğunda artışa neden olan hareket bozukluğu ise ç çe ek ki il lm me e d di is sk ki in ne ez zi is si i veya geri döndürülebilir diskinezi olarak adlandırılmaktadır.…”
Section: Geç Di̇ski̇nezi̇unclassified